2022
DOI: 10.1371/journal.pone.0272341
|View full text |Cite
|
Sign up to set email alerts
|

What is behind the gender gap in economics distance education: Age, work-life balance and COVID-19

Abstract: There is an ongoing debate about whether gender equality in education has been achieved or not. Research efforts have focused on primary and secondary education, while there are fewer studies on higher education, and few studies refer to distance education. To contribute to address this gap, this article presents a gender analysis of educational outcomes in economics at Spain’s leading distance university, UNED, which is also the largest university in the European Union in terms of enrolment. The aim of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These results are confirmed also for low-income, first-generation, and minority students. Castellanos-Serrano et al 14 focus on the academic consequences of the Covid-19 in gender inequalities by several education performances. They consider 7477 students enrolled in just one faculty from the 2016/2017 to 2020/2021 academic years.…”
Section: Tertiary Education and The Pandemicmentioning
confidence: 99%
“…These results are confirmed also for low-income, first-generation, and minority students. Castellanos-Serrano et al 14 focus on the academic consequences of the Covid-19 in gender inequalities by several education performances. They consider 7477 students enrolled in just one faculty from the 2016/2017 to 2020/2021 academic years.…”
Section: Tertiary Education and The Pandemicmentioning
confidence: 99%
“…However, studies have shown that online learning is as effective as face-to-face instruction and broadens access and participation in STEM and higher education (Means et al, 2014;Drew et al, 2015Drew et al, , 2016Ardissone et al, 2020Ardissone et al, , 2021. Interestingly, one of few studies directly examining the pandemic's impact on students in online programs, Castellanos-Serrano et al (2022) showed that the gender gap narrowed during lockdown, which was attributed to improved task sharing abilities with both men and women at home but was worse after lockdown compared to pre-pandemic, pointing to unequal social constraints impacting student achievement. Also, much attention has been focused on the lessons learned from the pandemic on innovative approaches to increasing support, access, and inclusion to and reimagining STEM education through a remote modality (Bhagat and Kim, 2020;Maqableh and Alia, 2021;Mohammed et al, 2021;Selco and Habbak, 2021;Manier et al, 2022).…”
Section: Introductionmentioning
confidence: 99%